Chromate Allergy in Northern Israel in Relation to Exposure to Cement and Detergents. Issue 3 (May 2016) - Kridin, Khalaf; Bergman, Reuven; Khamaisi, Mogher; Weltfriend, Sara
Abstract : Background: The prevalence of chromate allergy has declined worldwide in the last decades. Objectives: The aim of the study was to assess tendencies in chromate allergy in northern Israel and its possible causes. Methods: Retrospective analysis of patch test data during 1999-2013 and a review of the medical records of patients with chromate allergy were conducted. Results: A total of 4846 consecutive patients were patch tested, of whom 146 (3%) were found to be chromate sensitive. The prevalence of chromate allergy decreased significantly from 4.7% in 1999–2001 to 2.8% in 2002–2004 ( P = 0.02). Since then, no significant fluctuations have occurred. A gradual and consistent decline in chromate allergy was recorded among women from 4.8% in 1999–2001 to 2.3% in 2008–2010. Cement (18.4%) was the most frequent source of exposure and was mainly observed in men. The frequency of clinically relevant cement exposure increased significantly from 7.7% in 2002–2004 to 28.7% in 2011–2013 ( P = 0.04), whereas the frequency of relevant detergent exposure decreased significantly from 25% in 1999-2001 to 5.7% in 2011–2013 ( P = 0.04). Hand (68.5%) was the most frequently involved anatomical site. Conclusions: The prevalence of chromate allergy in northern Israel is stable in the general population and gradually decreasing among women. These changes may be caused by reduced exposure to water-soluble hexavalent chromium in detergents but not in cement.